Methods of Teaching the Qur’an at the Rumah Tahfiz Andalusia - Nanda Fadhillah; Cici Nopriza; Yusriani Yusriani; Efendi Efendi; Mutathahirin Mutathahirin (International Journal of Multidisciplinary Research of Higher Education, 2022)
Memorizing the Qur’an has been an integral part of the religious practice of Muslims since the time of the Prophet Muhammad. Memorizing the Qur’an is considered a noble act of worship and a noble achievement. The process of memorizing the Qur’an involves serious efforts in memory, understanding, and various methods. This study aims to analyze the teaching methods used in Rumah Tahfiz Andalusia. This study uses a qualitative method with a type of phenomenological research. Data sources were taken from two informants using an interview protocol. Data analysis techniques consist of data reduction, presentation, and leverage. Overall the results of the analysis show that there are five methods used in memorizing the Qur'an at Rumah Tahfiz Andalusia, namely: i) the Talaqqi method, ii) the iqra' method, iii) the tartil method. The results of this study have also proven that memorizing the Qur'an requires an appropriate and appropriate method